Analisis Faktor Keberhasilan Proyek Modernisasi Dan Rehabilitasi D.I Saddang Sub Unit Langnga (SIMURP) Kabupaten Pinrang - Iswandi L; Rahmawati Rahmawati; Andi Bustan Didi; Adnan Adnan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study aims to determine the influence of cost factors in determining the success of the modernisation and rehabilitation project in saddang sub unit langnga pinrang district, determine the influence of time factors in determining the success of the modernisation and rehabilitation project in saddang sub unit langnga pinrang district. determine the influence of quality factors in determining the success of the modernisation and rehabilitation project in saddang sub unit langnga pinrang district, determine the influence of health, safety and environmental factors in determining the success of the modernisation and rehabilitation project in saddang sub unit langnga pinrang district. This research was conducted using quantitative analysis, namely through distributing questionnaires and interviews to the owner, the contractor and the consultant, Data analysis carried out on the questionnaire collected using skinative statistics, namely the percentage to determine the main factors of the success of a project using the Statistical Package for The Social Sciens program.